Short Communication: New record of Linum austriacum var. album from Iran - SEYED MEHDI TALEBI; MASOUD SHEIDAI; MITRA NOORI (Nusantara Bioscience, 2016)
Abstract. Talebi SM, Sheidai M, Noori M. 2016. Short Communication: New record of Linum austriacum var. album from Iran. Nusantara Bioscience 8: 174-179. Different infraspecific taxa were described for Linum austriacum in various flora all over the world, while no verity/subspecies was recorded for this species in Iran. In the present study, for the first time, a new variety of the species, in the name of L. austriacum var. album were introduced for Iran. This variety was found in near Famenin city in Hamadan province. Comparison of morphological and phytochemical traits of var. album with its two nearest taxa, Linum austriacum var. austriacum and L. glaucum, showed that the main morphological difference of this variety with L. austriacum var. austriacum was the petal color, however most of morphological characteristics of var. album were bigger than var. austriacum. In addition, the kinds, as well as amount of flavonoids, differed between the studied taxa